Vpliv pakiranja zgorevalne zmesi na potek sinteze pri citratno nitratnem postopku - Zupan, Klementina (Materiali in tehnologije, 2000)
A citrate-nitrate gel combustion reaction was used for the submicron crystalline strontium substituted lanthanum cromite (LSC) preparation. The influence of the reaction mixture packing prior combustion for the different fuel contents on the reaction temperature and reaction period, phase formation and specific surface area of so prepared powders was investigated. It was shown that the reaction period depends on fuel/oxidant ratio and reaction mixture packing. The reaction duration time was few seconds for the loose packed layer prepared samples and few tens of seconds for samples prepared from the pallete, respectively. The nature of the agglomerates formation was studied by SEM in the green compacts pressed at 300 MPa. Thermal analysis was used to determine degree of conversion for as prepared samples.
Keywords: lantanov kromit; zgorevanje; sinteza